Genetic and enzymatic characterization of 3-O-sulfotransferase SNPs associated with Plasmodium falciparum parasitaemia. (28th April 2018) - Nguyen, Ngoc Thy; Vivès, Romain R; Torres, Magali; Delauzun, Vincent; Saesen, Els; Roig-Zamboni, Véronique; Lortat-Jacob, Hugues; Rihet, Pascal; Bourne, Yves
Abstract: The HS3ST3A1/B1 genes encode two homologous 3- O -sulfotransferases involved in the late modification step during heparan sulfate (HS) biosynthesis. In addition to the single nucleotide polymorphisms (SNPs) rs28470223 (C > T) in the promoter region of both HS3ST3A1 and rs62636623 (Gly/Arg) in the stem region of HS3ST3B1, three missense mutations (rs62056073, rs61729712 and rs9906590) located within the catalytic sulfotransferase domain of 3-OST-B1 are linked and associated to Plasmodium falciparum parasitaemia. To ascertain the functional effects of these SNP associations, we investigated the regulatory effect of rs28470223 and characterized the enzymatic activity of the missense SNP rs61729712 (Ser279Asn) localized at proximity of the substrate binding cleft. The SNP rs28470223 results in decreased promoter activity of HS3ST3A1 in K562 cells, suggesting a reduced in vivo transcription activity of the target gene. A comparative kinetic analysis of wt HS3ST3B1 and the Ser269Asn variant (rs61729712) using a HS-derived oligosaccharide substrate reveals a slightly higher catalytic activity for the SNP variant. These genetic and enzymatic studies suggest that genetic variations in enzymes responsible of HS 3- O- sulfation can modulate their promoter and enzymatic activities and may influence P. falciparum parasitaemia.